Teen Titans go! Volume 1, Party, party! - Fisch, Sholly (DC Comics, 2015)
Follows the adventures of Teen Titans Robin, Starfire, Cyborg, Raven, and Beast Boy as they battle a pizza monster, a video game console, and various super-villains.